Physical properties of Liberica coffee (Coffea liberica) berries and beans - Ismail, Iryane; Anuar, Mohd Shamsul; Shamsudin, Rosnah (Universiti Putra Malaysia Press, 2014)
Liberica coffee is the most important coffee species grown in Malaysia. However, there is little or no research at all conducted on coffee berries and green coffee beans since the plant itself is a low income crop in Malaysia. Therefore, research on Malaysian Liberica coffee can help to increase the knowledge of coffee farmers and coffee manufacturers in the processing and handling of the coffee. Physical properties of Liberica coffee berries and beans were investigated the current study. The properties investigated include the size, mass, density, coefficient of friction, angle of repose, fracture force and colour. In comparison to Arabica and Robusta coffee, Liberica coffee has the biggest size, mass, true density and fracture force values but were lower in bulk density in both berries and beans. The Liberica berries and beans were found to be orange-ish and yellowish colour respectively. Angle of repose was low and approximately similar in berries and beans while jute fibre gave the highest friction to both Liberica berries and beans.